The performativity of surveys: Teenagers’ meaning‐making of the 'Health Behavior in School‐aged Children Survey' in Sweden - Wickström, Anette; Zeiler, Kristin (Children & society, 2021)
The Health Behaviour in School‐Aged Children survey contains scales intended to measure life satisfaction, mental health problems and socioeconomic status. This article takes inspiration from science and technology studies and analyse the survey as performative. It also examines subjective meaning‐making through an analysis of interviews with 15‐year‐old teenagers. It shows how the survey enacts the subject position of an accountable teenager and how teenagers experience the survey as sending a message about how one should live. While some teenagers experience this as positive, others narrate feelings of shame. This could be interpreted as a way for them to be accountable for themselves.